Pan - Dehmel, Richard; Bierbaum, Otto Julius; Meier-Graefe, Julius (Berlin : Verlag Pan, 1895)
One of the most important voices of Art Nouveau in Germany. Edited by Otto Julius Bierbaum and Julius Meier-Graefe, the journal published numerous illustrations by well-known, and also unknown, young international artists. Additionally, there were full-page original designs, a simple modern typeface, vignettes and other forms of illustration.Some of the more well-known artists who published in PAN include Peter Behrens, Franz von Stuck, Max Klinger, Käthe Kollwitz, Auguste Rodin, Paul Signac and Félix Vallotton. Like the journal Jugend, PAN was critical about the artistic policy of the German Empire under Wilhelm. The journal attempted to present the very best of contemporary art, without showing preference for any particular school or movement, in order to allow comparison with classical art.(uit: https://www.ub.uni-heidelberg.de/Englisch/helios/fachinfo/www/kunst/digilit/artjournals/pan.html)
Online https://www.ub.uni-heidelberg.de/helios/fachinfo/www/kunst/digilit/artjournals/pan.html
Https://bluemountain.princeton.edu/exist/apps/bluemountain/title.html?titleURN=bmtnabe
Duits
Tijdschriften
Keywords: art nouveau